Performance of an Eco‐Driving Model Predictive Control System for HEVs during Car Following. Issue 1 (27th May 2015) - Yu, Kaijiang; Liang, Qing; Hu, Zhiguo; Yang, Junqi; Zhang, Hongwei
Abstract: This paper presents a model predictive control approach for the energy management problem of hybrid electric vehicles (HEVs) with variable time headway during car following. The new features of this study are as follows. First, a new method using model predictive control with fixed time headway is proposed to improve fuel economy outside the HEV. Second, the battery state of charge profile is scheduled systematically to improve fuel economy inside the HEV compared with the vehicle spacing influence outside the HEV. Computer simulation results are shown using the approaches with variable time headway and fixed time headway. The conclusion is that the model predictive control approach is effective for the energy management problem of the HEV system during car following.